Treatment with Cladribine Tablets Beyond Year 4: A Position Statement by Southeast European Multiple Sclerosis Centers - Habek, Mario; Drulovic, Jelena; Brecl Jakob, Gregor; Barbov, Ivan; Radulovic, Ljiljana; Rajda, Cecilia; Rejdak, Konrad; Turčáni, Peter (Springer Science and Business Media LLC, 2023)
Based on the results of the pivotal CLARITY study, cladribine tablets were approved for use in the European Union in 2017 as a high-efficacy therapy for highly active relapsing-remitting multiple sclerosis (MS). Cladribine tablets are used as an induction therapy: half of the total dose is given in year 1 and the other half in year 2. In the CLARITY Extension trials, repeating the dose routinely in years 3 and 4, was not associated with significantly improved disease control. However, there is very limited evidence on how to manage people with MS (pwMS) beyond year 4, which is increasingly important because more and more patients are now ≥ 4 years after cladribine treatment. Overall, postapproval data show that treatment with two cladribine cycles effectively controls disease activity in the long term. However, there is general agreement that some pwMS with suboptimal response could benefit from retreatment. This study reviews the practical aspects of using cladribine tablets, summarizes the evidence from clinical trials and real-world studies on the safety and efficacy of cladribine, and proposes a treatment algorithm developed by expert consensus for pwMS previously treated with cladribine. In brief, we propose that additional courses of cladribine tablets should be considered in patients with minimal (no relapses, 1-2 new lesions) or moderate (1 relapse, 3-4 new lesions) disease activity, while significant disease activity (> 1 relapse, > 3 new lesions) or progression should warrant a switch to another high-efficacy treatment (HET). More evidence is needed to improve the treatment guidelines for pwMS who previously received cladribine.